Evaluating RGB channels in remote photoplethysmography: a comparative study with contact-based PPG - Ontiveros, Rodrigo Castellano; Elgendi, Mohamed; Missale, Giuseppe; Menon, Carlo (Frontiers in Physiology, 2023)
Remote photoplethysmography (rPPG) provides a non-contact method for measuring blood volume changes. In this study, we compared rPPG signals obtained from video cameras with traditional contact-based photoplethysmography (cPPG) to assess the effectiveness of different RGB channels in cardiac signal extraction. Our objective was to determine the most effective RGB channel for detecting blood volume changes and estimating heart rate. We employed dynamic time warping, Pearson's correlation coefficient, root mean squared error, and Beats-per-minute Difference to evaluate the performance of each RGB channel relative to cPPG. The results revealed that the green channel was superior, outperforming the blue and red channels in detecting volumetric changes and accurately estimating heart rate across various activities. We also observed that the reliability of RGB signals varied based on recording conditions and subject activity. This finding underscores the importance of understanding the performance nuances of RGB inputs, crucial for constructing rPPG signals in algorithms. Our study is significant in advancing rPPG research, offering insights that could benefit clinical applications by improving non-contact methods for blood volume assessment.Keywords Remote photoplethysmography (rPPG) • blood volume pressure (BVP) • performance evaluation • RGB signals • Red, Green, Blue channels